(untitled) (Journal of Environmental Science and Natural Resources, 2013)
The present investigation reports on the fisheries status and marketing systems in Shaheb Bazar, Luxmipur, New Market and Shalbagan fish markets under the Rajshahi City Corporation Area. More than 35-40 species of fishes under 8-10 orders and the Shaheb bazaar fish market. About 30 species of fishes under 7-8 orders are also found in and Shalbagan and Luxmipur fish market, respecfively the limitations of the fish markets have been pin-pointed and their methods of improvement suggested. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14822 J. Environ. Sci. & Natural Resources, 5(2): 245-250 2012